Zebrafish as an Emerging Model Organism to Study Angiogenesis in Development and Regeneration - Chávez, Myra N.; Aedo, Geraldine; Fierro, Fernando A.; Allende, Miguel L.; Egaña, José T. (Frontiers in Physiology, 2016)
Angiogenesis is the process through which new blood vessels are formed from preexisting ones and plays a critical role in several conditions including embryonic development, tissue repair and disease. Moreover, enhanced therapeutic angiogenesis is a major goal in the field of regenerative medicine and efficient vascularization of artificial tissues and organs is one of the main hindrances in the implementation of tissue engineering approaches, while, on the other hand, inhibition of angiogenesis is a key therapeutic target to inhibit for instance tumor growth. During the last decades, the understanding of cellular and molecular mechanisms involved in this process has been matter of intense research. In this regard, several in vitro and in vivo models have been established to visualize and study migration of endothelial progenitor cells, formation of endothelial tubules and the generation of new vascular networks, while assessing the conditions and treatments that either promote or inhibit such processes. In this review, we address and compare the most commonly used experimental models to study angiogenesis in vitro and in vivo. In particular, we focus on the implementation of the zebrafish (Danio rerio) as a model to study angiogenesis and discuss the advantages and not yet explored possibilities of its use as model organism.